Serão os não humanos os últimos “outros” na Antropologia? Representações sobre a superioridade humana - Casanova, Catarina (Trabalhos de Antropologia e Etnologia, 2020)
This paper aims to address a short overview of the discussion topics surrounding the false paradigm “nature” vs. “culture” pointing the biological positioning of the human species (Homo sapiens sapiens) and mentioning bias visions in what regards theocentric and anthropocentric perspectives. Mentioning the responsibility of Anthropology to deconstruct the false paradigm of “nature” and “culture”, interdisciplinary is discussed as well as the assumptions underpinning contemporary biological anthropology. Scientific data shows that there is continuity between all primates (humans included) in what regards genotype and phenotype. Addressing the false dichotomy on which the Judeo-Christian paradigm prevails, this text seeks to develop the chimpanzee (Pan troglodytes) example referring to important aspects of the ethnography of this species such as their political behaviour, their material culture, among other behaviours and features.